Professionalizing teacher education accountability - Mayer, DE (Oxford University Press, 2017)
This article examines teacher education accountability and argues for new emphases in accreditation and beginning teacher certification designed to professionalize teacher education. A brief overview of the history of teacher education policy is presented as a background framing for exploring the current policy moment positioning teacher education as a problem that needs to be fixed. Government responses discussed are mainly those in the Anglophone areas of Australia, North America, and the United Kingdom. These involve tighter regulation while at the same time opening up a deregulated teacher education environment as well as an increasing focus on measuring the contribution that teacher preparation makes to student learning. The article suggest ways of professionalizing teacher education accountability which go beyond the “partnerships,” “classroom-ready,” and “value-added” mantras of current debates and policies and considers (1) teacher education in a new hybrid space, (2) authentic graduate assessments, and (3) rigorous research evidence as the cornerstones of a refreshed and more professionalised approach to teacher education accountability.